Prediabetes as a risk factor for major adverse cardiovascular events. (1st January 2021) - Mando, Ramy; Waheed, Muhammad; Michel, Adrian; Karabon, Patrick; Halalau, Alexandra
Abstract: Introduction: Type II diabetes mellitus (DM) is a proinflammatory process and a known risk factor for major adverse cardiac events (MACE). The same inflammatory markers may be present in prediabetes (pDM); however, the relationship between pDM by HbA1c and MACE is not well studied. We sought to see if pDM increases one's risk for MACE. Methods: We retrospectively studied patients at Beaumont Health, Michigan between 2006 and 2020. We divided patients into groups (G1–G5) based on haemoglobin A1c (HbA1c) trends over the study period as follows: G1: pDM patients who remained pDM; G2: pDM who progressed into DM; G3: pDM who normalized their HbA1c; G4: patients who maintained a normal HbA1c; and G5: patients with HbA1c persistently in the DM range. We compared MACE between the groups by univariate and multivariate regression analyses. Results: A total of 119, 271 patients were included in the study (G1: N  = 13, 520, G2: N  = 6314, G3: N  = 1585, G4: N  = 15, 018, G5: N  = 82, 834). Pairwise comparison revealed a statistically significant increase in the odds of MACE in all groups compared to those with normal HbA1c values (G4; p  < .001). After adjusting for baseline characteristics, multivariate regression revealed elevated odds of MACE in patients with persistent pDM (G1; aOR = 1.087, p  = .002) and diabetes (G2/G5; aOR = 1.25 and aOR = 1.18, p  < .001) compared to individuals with normal HbA1c values. Conclusion: Prediabetes is a risk factor for MACE. Normalization of HbA1c values appears to decrease the adjusted risk for MACE and should be the goal in patients with pDM. KEY MESSAGES: Patients with prediabetes (pDM) are at increased risk for major cardiovascular events. Normalization of HbA1c in pDM patients may have a clinically significant benefit, in terms of lowering the MACE risk. Prediabetes patients who progress into diabetes mellitus may represent a particularly high-risk group.